PERNIKAHAN YANG TIDAK DICATATKAN DAN PROBLEMATIKANYA - Ma’sum, H. Endang Ali (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
Marriage is essentially much more than an akad (agreement) allowing for sexual relations between husband and wife, but is the vocal point of communal life. Therefore, marriage holds an important meaning in human life and forms the cultural patterns to create and control strong foundations in domestic life. In its secondary function, marriage becomes the pillar for a larger order in social life, from the communal to the national level. Therefore, legal and administrative order must be implemented, among them the registration of marriage. An unregistered marriage causes negative consequences for the marriages itself, to the children born from that marriage and the corresponding legal issues. Therefore, this article pushes for courage on behalf of the ulama to insert marital registration as a rukun (religious requirement) for marriage in accordance with Indonesian fiqh, to clarify that unregistered marriages are illegal and to push the Indonesian public to consider such instances with greater scrutiny.